(untitled) (Analysis in Theory and Applications, 2017)
In this paper, we introduce the concept of generalized g-quasi-contractions in the setting of cone b-metric spaces over Banach algebras. By omitting the assumption of normality we establish common fixed point theorems for the generalized g-quasi-contractions with the spectral radius r(λ) of the g-quasi-contractive constant vector λ satisfying r(λ) [0,1s) in the setting of cone b-metric spaces over Banach algebras, where the coefficient s satisfies s1. The main results generalize, extend and unify several well-known comparable results in the literature.